Dissociation of mitochondrial and ribosomal biogenesis during thallium administration in rat kidney. - Sho Sugahara; Kana Unuma; Shuheng Wen; Takeshi Funakoshi; Toshihiko Aki; Koichi Uemura (PLoS ONE)
Thallium (Tl) is a heavy metal with toxicity comparative to other heavy metals such as As, Cd, and Hg. Nevertheless, fewer studies have been reported concerning the molecular mechanism of Tl toxicity as compared to other heavy metals. To obtain insight into Tl toxicity in the kidney, rats were intraperitoneally administered Tl2SO4 (30 mg/kg), and the kidneys were removed 2 or 5 days later to examine the effects of Tl. Transcriptome analysis using DNA microarray of the rat kidney 2 and 5 days after Tl administration showed that cytoplasmic ribosomal proteins are the most upregulated category; many of the genes involved in ribosome biosynthesis were upregulated by Tl administration. This upregulation was associated with the activation of eukaryotic transcription initiation factor 2α (eIF2α), implying that increased ribosome biogenesis was linked to the subsequent activation of protein translation. In contrast, decreased mitochondrial biogenesis was revealed via proteomic analysis. Although we found an increase in Myc, a positive regulator of both ribosomal and mitochondrial biogenesis, decreased levels of NRF1 and TFAM, positive regulators of mitochondrial biogenesis whose gene expression is directory activated by Myc, were paradoxically observed. Taken together, differing responses of ribosomes and mitochondria to Tl toxicity were observed. Failure of transmission of the Myc signal to NRF1/TFAM might be involved in the observed disruption of coordinated responses in mitochondria and ribosomes during Tl administration in rat kidney.